Perilla frutescens Leaf Extract and Fractions: Polyphenol Composition, Antioxidant, Enzymes (α-Glucosidase, Acetylcholinesterase, and Tyrosinase) Inhibitory, Anticancer, and Antidiabetic Activities - Zhenxing Wang; Zongcai Tu; Xing Xie; Hao Cui; Kin Weng Kong; Lu Zhang (Foods, 2021)
This study aims to evaluate the bioactive components, in vitro bioactivities, and in vivo hypoglycemic effect of P. frutescens leaf, which is a traditional medicine-food homology plant. P. frutescens methanol crude extract and its fractions (petroleum ether, chloroform, ethyl acetate, n-butanol fractions, and aqueous phase residue) were prepared by ultrasound-enzyme assisted extraction and liquid–liquid extraction. Among the samples, the ethyl acetate fraction possessed the high total phenolic (440.48 μg GAE/mg DE) and flavonoid content (455.22 μg RE/mg DE), the best antioxidant activity (the DPPH radical, ABTS radical, and superoxide anion scavenging activity, and ferric reducing antioxidant power were 1.71, 1.14, 2.40, 1.29, and 2.4 times higher than that of control Vc, respectively), the most powerful α-glucosidase inhibitory ability with the IC50 value of 190.03 μg/mL which was 2.2-folds higher than control acarbose, the strongest proliferative inhibitory ability against MCF-7 and HepG2 cell with the IC50 values of 37.92 and 13.43 μg/mL, which were considerable with control cisplatin, as well as certain inhibition abilities on acetylcholinesterase and tyrosinase. HPLC analysis showed that the luteolin, rosmarinic acid, rutin, and catechin were the dominant components of the ethyl acetate fraction. Animal experiments further demonstrated that the ethyl acetate fraction could significantly decrease the serum glucose level, food, and water intake of streptozotocin-induced diabetic SD rats, increase the body weight, modulate their serum levels of TC, TG, HDL-C, and LDL-C, improve the histopathology and glycogen accumulation in liver and intestinal tissue. Taken together, P. frutescens leaf exhibits excellent hypoglycemic activity in vitro and in vivo, and could be exploited as a source of natural antidiabetic agent.